The Effect of Organizational Culture and Work Motivation on the Performance of Cooperative Services and MSME Officers, Banjar Regency, South Kalimantan - Kadir, Abdul; Audah, Ali; Jayen, Fredy; Amrulloh, Rifqi; Naimah (Archives of Business Research, 2023)
This study aims to analyze the influence of organizational culture and work motivation on the performance of the Department of Cooperatives and SMEs in Banjar Regency, South Kalimantan. The population in this study comprised 33 employees of the Department of Cooperatives and SMEs in the Banjar Regency, South Kalimantan. A total sampling technique was used the total sampling technique, and the sample was collected from the entire population of 33 people. This study used the correlational method to compare and determine the relationship between organizational culture variables and work motivation on the performance of the Cooperative and SMES Employee Service Office in Banjar Regency, South Kalimantan. The data analysis in this study used multiple linear regression analysis, whereas hypothesis testing used partial t-tests and simultaneous F-tests. The results showed that simultaneously and partially organizational culture and work motivation have a significant effect on the performance of the Department of Cooperatives and SMEs in Banjar Regency, South Kalimantan. The Organizational Culture variable had a dominant influence compared to the work motivation variable.